(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
The undesirable adverse effects of present available synthetic drugs endorse the modern medicine to search the superior choice for the treatment of metabolic diseases. Herbal medicine turns out to be a hopeful therapy for the effective treatment of diabetes in foreseeable future. In an effort to render a scientific evidence for the antidiabetic potential of Annona reticulata L., the present research, with the objective to evaluate the ability of A. reticulata leaf extracts on antihyperglycemic property under in vitro using yeast cell model was performed. Besides, as the diabetes and its complications are highly associated with the oxidative stress, the current study was also focussed on antioxidant property of A. reticulata leaf extracts. The scavenging ability of plant extracts on free radical 2, 2 – diphenyl- 1- picrylhydrazyl (DPPH), ferric reducing power assay and total antioxidant activity were performed to establish the antioxidant potential of A. reticulata leaf extracts. The in vitro antidiabetic ability of A. reticulata leaves was evaluated by glucose uptake method using yeast cell model. Among the four chosen solvent extracts- aqueous, methanol, ethyl acetate and n-hexane, methanol extract (MeE) exhibited high antioxidant potential. MeE exhibited 62.28% of DPPH inhibition at 200µg/ml, with total antioxidant activity 164.72 ± 2.63µg/ml and higher absorbance in reducing power assay (1.15 ± 0.03). In vitro antidiabetic activity by glucose uptake of yeast cell assay was evaluated and observed dose dependant rise in % of glucose uptake in methanol, ethylacetate and aqueous extracts of A. reticulata. MeE showed 48.55% of glucose uptake at 500µg/ml concentration. Hence the present study could be concluded as A.reticulata leaves possess potent antioxidant activity and antidiabetic activity under in vitro conditions. With the outcome of the present initial study, research work could be extended further; thereby the exact pharmacological action of the plant compounds could be discovered.